Manajemen Isu Penetapan Kuota Haji Tambahan oleh Kementerian Agama dalam Penyelenggaraan Haji Tahun 1445 H/ 2024 M - Yulianto, Dhamar (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Research on the issue management of the determination of additional hajj quotas by the Ministry of Religion in the Implementation of the Hajj in 1445 H/2024 M is an interesting topic. Based on the results of searching for articles published in 2014-2024 with the keywords "Ministry of Religion", "Hajj Quota", and "Issue Management" using the Garuda Kemdikbud search engine and Research Gate from September 15 to October 15, 2024, there has been no research that specifically discusses this matter. This study aims to determine the five stages of issue management regarding the determination of additional hajj quotas by the Ministry of Religion in the Implementation of the Hajj in 1445 H/2024 M. The research method uses qualitative descriptive case studies to determine the five stages of issue management by the Ministry of Religion as in the Issue Management Theory by Chase and Jones. The results are that the Ministry of Religion carries out issue identification, issue analysis, program formulation, program implementation, and program evaluation, so that the image of the institution is maintained and does not cause an ongoing crisis. This research is useful for various groups, especially as a reference for the stages of issue management amidst the lack of references on the topic.